Studi Konsentrasi Kalium Hidroksida (KOH) Terhadap Kualitas Karbon Aktif Tempurung Kluwak - Faisal Faisal; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The objective of this research was to study the effect of potassium hydroxide (KOH) activator on characteristics of kluwak shell active carbon. This research was conducted experimentally by used Complete Randomized Design (CRD) with five treatments and three replications which followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatments of this study were P1 (KOH activator 5%), P2 (KOH activator 10%), P3 (KOH activator 15%), P4 (KOH activator 20%) and P5 (KOH activator 25%). The results showed that addition of various concentrations of KOH activators significantly affected moisture content, volatile matter, ash content, pure carbon content and adsorption on iodine. Based on the results of the research, P1 (KOH activator 5%) was chosen as the best treatment which moisture content 8.53%, volatile matter 8.69%,ash content 8.73%, pure carbon content 82.59% and adsorption on iodine 1510.47 mg/g.Keywords:active carbon, kluwak, potassium hydroxide